Short-Term And Long-Term Effects of United Nations Peace Operations - Sambanis, Nicholas, 1967- 1967- (The World Bank, 2007)
Earlier studies have shown that United Nations peace operations make a positive contribution to peacebuilding efforts after civil wars. But do these effects carry over to the period after the peacekeepers leave? And how do the effects of UN peace operations interact with other determinants of peacebuilding in the long run? The author addresses these questions using a revised version of the Doyle and Sambanis dataset and applying different estimation methods to estimate the short-term and long-term effects of UN peace missions. He finds that UN missions have robust, positive effects on peacebuilding in the short term. UN missions can help parties implement peace agreements but the UN cannot fight wars, and UN operations contribute more to the quality of the peace where peace is based on participation, than to the longevity of the peace, where peace is simply the absence of war. The effects of UN missions are also felt in the long run, but they dissipate over time. What is missing in UN peacebuilding is a strategy to foster the self-sustaining economic growth that could connect increased participation with sustainable peace